Relevance and applicability of ICF Core Sets for adults with cerebral palsy in low‐ and middle‐income countries. (18th November 2021) - Pathak, Anupa; Sharma, Saurab
Abstract : This commentary is on the original article by Noten et al. on pages 569–577 of this issue.